Rare case report of Asherman syndrome (Indian Journal of Case Reports, 2025)
Asherman syndrome, also known as intrauterine adhesions (IUAs), is a rare but significant gynecological condition. IUAs develop from the damage to the basal layer of the endometrium, leading to the formation of fibrous adhesions within the uterine cavity. Most commonly, it is followed by uterine surgeries, such as dilation and curettage, particularly following pregnancy-related procedures, and can also occur after hysteroscopic surgery, uterine artery embolization, or uterine tuberculosis. This syndrome causes changes in the menstrual cycle and affects the fertility of patient. Here, we report a case of Asherman syndrome that was not followed by any medical illness or surgical procedure for a gynecological or obstetric condition, or postpartum complication.